PENERAPAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA KELAS VI DI SDN 16 SUNGAI PINYUH - Hayati, Nur; Setyowati, Dessy; Farisi, Salman Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) activities within the context of the independent curriculum, as well as to explore how these activities can enhance students' competencies and character. The method used is qualitative descriptive research, with data collection through interviews and observations. The focus of this research includes the implementation of holistic, contextual, student-centered, and exploratory principles (P5).In the implementation of the Pancasila Student Profile Strengthening Project (P5), students are invited to participate in various activities relevant to the theme "Unity in Diversity," aimed at developing Pancasila character and enhancing tolerance among students from diverse backgrounds. The research findings indicate that the implementation of (P5) at SDN 16 Sungai Pinyuh not only increases active student engagement but also strengthens Pancasila values in daily life.Teachers act as facilitators who support students in the learning process, encouraging them to explore and collaborate in solving problems in their environment. Data analysis shows that students demonstrate positive changes in attitudes and behaviors, such as increased environmental awareness, cooperative attitudes, and critical thinking skills